Analysis of Avgas Fuel Spraying Schemes Using the ANSYS Application Approach - Putra, Dimas Endrawan; Ilminnafik, Nasrul; Hentihu, M Fahrur Rozy; Kustanto, Muh. Nurkoyim; Yudistiro, Danang; Syuhri, Skriptyan N.H. (Journal of Mechanical Engineering Science and Technology (JMEST), 2024)
Avgas fuel consumption on Cessna trainer aircraft is very high. However, there has been little research regarding spray impacts in Cessna aircraft engines. The phenomenon of avgas spray colliding with the cylinder wall may occur during fuel injection, resulting in a changed spray radius and height, which will affect the mixing of fuel and air. In several aspects, this affects engine performance and exhaust emissions on Cessna aircraft. This research aims to determine and study the phenomenon of spray impact on avgas-fueled aircraft engines. The fuel spray in the study occurred in the combustion chamber using pressure from a fuel hand pump whose pressure was supplied from a compressor with a pressure adjusted to the original pressure on the aircraft, namely 2 Bar (30 Psi). The experiments in this research used a high-speed camera system to study the phenomenon of avgas spray on walls to get better spray distribution. The results of this research were processed using the CFD application. The result of this research is that the greater the pressure, the more concentrated the resulting jet will be on the jet wall so that the atomization of the fuel jet will be dispersed. When the burst occurs, a change of 3.80e+00 occurs compared to other burst pressures.